A Pragmatic Analysis On Directive Utterances Used In Donald Duck Comics Manuscript - ANWAR, SAIFUL (2012)
This research paper aims at describing the language form, the politeness strategy, and the intention of directive utterances used in Donald Duck comics manuscript. To achieve the objectives, the writer refers to language form theory to identify the language from of directive utterances, Brown and Levinson's theory of politeness to identify the politeness strategy, Austin's theory of speech act to describe the intention of directive utterances. The type of this research is qualitative research. The method of collecting data is documentation method, and the steps are reading the comics, finding, noting, retyping, coding the data. The writer analyzes the data of directive utterances by using descriptive analysis. The result of the study shows that the language form of directive utterances in Donald Duck comics manuscript are positive declarative sentence(33.33%), negative declarative sentence (6.67%), positive imperative sentence (35.56%), negative imperative sentence (6.67%), positive interrogative sentence (13.33%), and negative interrogative sentence (4.44%). The politenes pattern used in Donald Duck comics manuscript are bald on record (42.22%), positive politeness (26.67%), negative politeness (24.44%), and off record (6.67%). The implicature of directive utterances used in Donald Duck comics manuscript belongs to conventional implicature, and the intention are commanding/ordering (33.33%), requesting (37.78%), prohibiting (6.67%), and suggesting (22.22%). Key words: Pragmatic, directive utterance, language form, politeness strategy, intention.